Presence of anti-neuronal antibodies in children with neurological disorders beyond encephalitis. (September 2020) - Nikolaus, Marc; Meisel, Christian; Kreye, Jakob; Prüss, Harald; Reindl, Markus; Kaindl, Angela M.; Schuelke, Markus; Knierim, Ellen
Abstract: Background: Anti-neuronal autoantibodies have been reported as the cause of several neurologic disorders other than encephalitis. Unfortunately, data are mostly based on serum analysis. Predictions about pathogenicity are thus limited. To determine the presence of so far unidentified autoantibody-derived neuroreactivity we analyzed cerebrospinal fluid (CSF) of children with neurological disorders other than encephalitis. Patients and methods: We did a retrospective analysis of CSF from 254 children with various neurologic diseases other than encephalitis and searched for reactivity against neuronal surface antigens by immunofluorescence on unfixed murine brain sections (tissue-based assay, TBA) and by commercial cell-based assays (CBA). A semi-quantitative fluorescence score classified our results and we described the clinical course of all positive patients with strong neuroreactivity. Results: Strong anti-neuronal IgG immunoreactivity of unknown antigen specificity was detected in CSF samples of 10 pediatric patients (4%, n = 10/254) with unsolved neurological disorders. CSF inflammatory markers were elevated. Most patients did not or only partly recover. Five screening-positive patients presented with a combination of headache and visual impairment due to optic nerve atrophy. Our data suggest to consider inflammatory, autoantibody-related etiologies, especially in cases without definite diagnoses. Conclusions: We present an overview of CSF neuroreactivity in children with neurological disorders other than encephalitis, indicating the presence of unidentified anti-neuronal autoantibodies. As TBA enables screening for unknown autoantibodies, we suggest this method as a second step if commercial CBAs do not yield a result. Further studies are necessary to characterize such antibodies, evaluate pathogenicity, and answer the question whether positive CSF neuroreactivity should prompt an immunotherapeutic approach.